2011
DOI: 10.2478/v10186-011-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Particle Filled Polyethylene Composites Used in the Technology of Rotational Moulding

Abstract: Particle Filled Polyethylene Composites Used in the Technology of Rotational Moulding The submitted article discusses rotational moulding technology and filled plastics. For testing, linear low density polyethylene filled with talc was used. The materials tested varied way of mixing the filler into the polymer. For the prepared samples were evaluated by tensile, elongation, melt flow index, density, Shore hardness and Vicat softening temperature. Experiments showed that, in principle, it is possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The initial VST for pure PE (117 • C) was the highest, while the heat resistance for the increasing WB content was lower, with the addition of 20% WB it was around 111 • C. Such a scale of changes can be considered small, but interestingly the addition of a filler causes thermal resistance folds. Previous research on the rotational molding technique partly overlaps with the obtained VST measurement results, where the addition of the filler did not significantly affect the heat resistance of the composite [55,56], or even worsened it [57]. Usually, the occurrence of significant material porosity is indicated as the main reason for the deterioration of materials properties of rotomolded composites [58].…”
Section: Thermomechanical Behaviormentioning
confidence: 88%
“…The initial VST for pure PE (117 • C) was the highest, while the heat resistance for the increasing WB content was lower, with the addition of 20% WB it was around 111 • C. Such a scale of changes can be considered small, but interestingly the addition of a filler causes thermal resistance folds. Previous research on the rotational molding technique partly overlaps with the obtained VST measurement results, where the addition of the filler did not significantly affect the heat resistance of the composite [55,56], or even worsened it [57]. Usually, the occurrence of significant material porosity is indicated as the main reason for the deterioration of materials properties of rotomolded composites [58].…”
Section: Thermomechanical Behaviormentioning
confidence: 88%
“…A decrease in MFR with increasing the filler content is associated with increased viscosity of the filled material, as well as with an increase in its density (Figure 12) caused by increasing the amount of quartz flour particles in the matrix of linear low-density polyethylene. This phenomenon is well-known and often described in the literature [ 35 , 36 ]. A probable cause of the reduction in MFR is the ability of filler particles to agglomerate, which results in a distorted flow of the polymer material in the platometer die flow channels.…”
Section: Resultsmentioning
confidence: 93%
“…Right choice of input parameters is very important and with influence on the mechanical characteristics and the final product [1,2,3,4,5,8]. For example Butora P., et al concluded it is necessary to choose optimal parameters of the polymer filler and the size of the particles, their dispersion and density [6].…”
Section: Introductionmentioning
confidence: 99%